Preparation and Optical Properties of Compound Nanopowder Art Ceramics - Yulan Li (International Journal of Analytical Chemistry)
The fluorescent glass of white LEDs has high physical and chemical stabilities, good heat dissipation performance, and can maintain an excellent performance of fluorescent powder itself. In order to realize luminescent materials such as white LED lighting, laser lighting, and long-term lighting, this study proposes the preparation of a compound nanopowder art ceramic and its optical properties. In order to play the role of nanoparticles in optoelectronic or photonic devices, it is necessary to explore the preparation process and performance research of dielectric ceramics. This study uses high-purity aluminate (MgAl2O4) powder for transparent ceramics, doped with yellow nanophosphor as raw materials, through a sintering process in oxygen atmosphere, sintering combined with heat treatment, and isostatic pressing to prepare transparent ceramics. The ceramic sample is placed in a high-temperature and high-pressure environment for heat and other static pressure, and fluorescent samples are obtained. The results show that under 350 mA driving current, high-power white LEDs in the fluorescent ceramic package have almost no attenuation after 700 h, and the average attenuation of the LED package of the phosphor package is about 10%. The use of fluorescent ceramics can be packaged not only to improve the LED device’s light efficiency but also to increase the life of the white LED device.